Contents of Boric Acid in Noodles and Processed Foods - Amit, Zunika; Lasem, Liwan Anak; Aabdul Rahamn, Muhd Hariz Luqman; Ahmad Rifen, Nur Nayli Nasuha; Abdul Muti, Nur Hazira; Ling, JIn Hui (Borneo Journal of Resource Science and Technology, 2020)
Boric acid is commonly used as pesticides, antifungal and antiseptics. It was also used as a food preservative to prolong the shelf life and enhance the food texture. In Malaysia, the addition of boric acid during food processing is prohibited due to its detrimental effect on health. In this study, noodles and fish-based processed food from different manufacturers were analysed for their boric acid concentrations by using the curcumin method. The results showed that there was high concentration of boric acid found in the noodles and fish-based processed food samples. The amount of boric acid detected in yellow noodles varied over the four weeks and amongst manufacturers. A similar pattern was also observed for ‘kuey teow’ (flat rice noodle) and ‘kolok’ noodle. The highest amount of boric acid concentrations was found in ‘kuey teow’ followed by yellow noodles and ‘kolok’ noodle. There was also inconsistency in the concentration of boric acid in fish cakes, fish balls and crab sticks. For fish-based products, crab stick contained the highest amount of boric acid followed by fish ball and fish cake. Even though the addition of boric acid to food is banned in Malaysia, the results of this study showed that boric acid is still being used as a food preservative in food manufacturing.